2015
DOI: 10.4103/0972-6748.181726
|View full text |Cite
|
Sign up to set email alerts
|

P300 latency as an indicator of severity in major depressive disorder

Abstract: Background:Depression is the most common mental health problem across all the age groups. Still diagnostic techniques and laboratory tests are awaited to confirm it. Some studies focus on P300 latency to aid in the diagnosis of depression. Hence, this study was conducted to know whether P300 latency is an indicator of major depressive disorder (MDD).Methods:This study was conducted both on patients admitted in the hospital and those attending outdoor clinic giving written informed consent and fulfilling inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 16 publications
1
20
2
Order By: Relevance
“…These data corroborate a study conducted in Australia that found greater amplitude and lower latency in patients with depression compared to those without depression, 41 and also another in India, that found a delay in latency among patients with depression compared to healthy controls, which was proportional to disease severity. 42 …”
Section: Discussionmentioning
confidence: 99%
“…These data corroborate a study conducted in Australia that found greater amplitude and lower latency in patients with depression compared to those without depression, 41 and also another in India, that found a delay in latency among patients with depression compared to healthy controls, which was proportional to disease severity. 42 …”
Section: Discussionmentioning
confidence: 99%
“…Similar to the P300 amplitude and depression literature, researchers have found that P300 latency is significantly delayed in depression -suggesting that P300 latency may also reflect an indicator of general cognitive impairments related to depression (Himani et al, 1999;Kalayam et al, 1998;Tripathi et al, 2015). For instance, Vandoolaeghe et al (1998) reported that currently depressed adults were characterized by prolonged P300 latency compared to controls.…”
Section: Introductionmentioning
confidence: 78%
“…[91] presents a review of EEG (Electroencephalograms) and ERP (Event-Related Potentials) based predictive biomarkers for MDD. This study highlights 1) Alpha power and asymmetry, 2) Theta band activations, 3) Antidepressant treatment response (ATR) index, 4) Theta QEEG cordance, 5) Referenced EEG (rEEG), 6) Rostral anterior cingulate cortex (rACC) activations and 7) machine learning as EEG based predictive biomarkers 8) The P300 [92] and LDAEP [93] as ERP biomarkers. Wake and sleep EEG is also used as a depression biomarker in [94] that provide an overview of sleep variations in depression.…”
Section: Biomarkers-based Assessment Of Clinical Depression (Assessme...mentioning
confidence: 99%